A correlation between the gas and liquid permeabilities of beech wood heat-treated in hot water and steam mediums - Reza Taghiyari, Hamid; Talaei, Aisona; Karimi, Ali (Maderas. Ciencia y Tecnología, 2025)
Heat-treatment, a major method of wood modification for improving dimensional stability and natural durability, has been studied considerably in the scientific literature. This study will focus on the effect of heat-treatment on permeability, an important physical property of wood by subjecting beech samples to two different mediums of hot water and steam, as well as in two buffered hot water of pH 7 and 8. Hydrothermal treatment caused gas permeability to decrease to its lowest value among the treatments (91.6% decrease comparing the control treatment). Hydrothermal treatment in buffered hot water of pH 8 made the lowest impact on gas permeability (12.3% decrease). The decrease in gas permeability was due to settlement of extractives on vessel perforation plates. Gas permeability showed a highly significant correlation with the amount of swelling in radial direction. Low correlation was found between liquid permeability with water absorption and the amount of swelling. Gas permeability is considered a suitable criterion for predicting the amount of swelling in beech wood.